Application Of Territorial Principles Against Pedophile Criminal Act Perpetrators Perpetrated By Foreign Citizens - Madamba, Wiranda Putri; Puluhulawa, Fenty Usman; Badu, Lisnawaty Wadju; Puluhulawa, Jufryanto; Moha, Mohamad Rivaldi (JURNAL LEGALITAS, 2021)
Indonesian criminal law adheres to various principles that form the basis for solving problems, especially in problems related to two or more countries. One of the principles recognized and in line with the research, in this case, is the territorial principle, which is a useful principle in determining the limits of validity of criminal law provisions based on place or location. This study aims to analyze the application of the territorial principle to perpetrators of pedophilia crimes committed by foreign nationals. The method used in this study is a normative type of research that uses the law approach and case studies. The results of this study indicate that should be based on the principle of criminal law, namely the territorial principle, Indonesian law will be applied to anyone who commits a crime in Indonesia, including in this case foreign citizens who commit pedophilia crimes, especially a sovereign state has exclusive jurisdiction in the environment. the territory itself is called territorial sovereignty so that the state has full jurisdiction to punish people who commit crimes against the law in the territory of the country. In reality, this territorial principle cannot be applied to this case because the suspect is still in the process of waiting for the results of approval or rejection of extradition by the Ministry of Law and Human Rights of the Republic of Indonesia, considering that the suspect is a foreign citizen and is also a fugitive in his home country, namely the United States of America. so that the country of origin sends a letter of request for extradition and this extradition request is still in the process of being followed up.